From mediation without interpreters to bilingual scribes. Diglossia, bilingualism and writing in the province of Chayanta (Potosí) during Bolivian Republic (1830-1950) - Platt, Tristan (2018)
Bilingualism made interpreters unnecessary in early RepublicanBolivia. Citizen judges of the Peace functioned as Spanish-Aymarabilingual scribes in Chayanta Province (Potosí), while new bilingualCitizen tribute-collectors (recaudadores) replaced hereditaryAymara-speaking moiety Curacas. In Peru and Ecuador tributewas abolished in the 1850s, but in Bolivia it continued till the 21stcentury. By the 20th century, Quechua had become the language ofthe Macha Ayllu, and the moieties took back the Curacazgos. Thisarticle examines the resurgence of the moiety Curaca Recaudadores,and their persistence as tribute’collectors for most of the 20thcentury. Macha moiety Curacas were illiterate, and monolingualin Quechua, but had Ayllu support, and could administer usingbilingual mestizo scribes. They formed a Spanish-language Archive,an invaluable source for building a Republican ethnohistory of 20thcentury rural literacy, Ayllu organization, social movements andAyllu-State relations. Among its 740 documents the Archive containsthree Aymara-influenced circulars from La Paz, written in aSpanish-derived linguistic amalgam between 1936 and 1946. Theyshed light on indian political thought in a period when the Ayllu-State pact and «indian law» were being recovered, before and afterthe Revolution of 1952.